Investigação da dinâmica de formação de gotas no interior de microcanais via técnicas de CFD - Chaves, Igor Lima (2020)
Microfluidics has a recent origin and its development is based on microanalytical methods. Defined as the science and technology that addresses the manipulation of small amounts of fluids flowing into channels of tens to hundreds of micrometers, microfluidics today has a diversity of applications due to their characteristics of control efficiency. In this work, the microfluidics applications are briefly addressed, the physical characteristics phenomena that govern it are elucidated by identifying the general flow characteristics, the relevant phenomena and dimensionless studies of flow in channels on the micro-scale, as well as the interfacial properties, which appear in multiphase systems. The mathematical basis used to study the flow phenomena is still addressed. Computational fluid dynamics (CFD) techniques are used as a methodology for development, to overcome the limits of laboratory experimentation (observed here the numerical control of the value for interfacial properties). For the study of multiphase microfluidic flows, the Multiphase Fluid Volume Model (VOF) is used, which allows the flow to be solved numerically and to observe its behavior through the interfaces between immiscible fluids. Given this, in this work, the VOF model was validated with experimental results, both quantitatively and qualitatively, to predict the entire process of generating drops within microchannels. Additionally, the Adaptive Mesh Refining (AMR) technique was used to better track the interface between the fluid phases. The effects of the microchannel geometry, the physical properties of the fluids and the operating conditions, on the size and rate of droplet generation were evaluated using the multiple regression techniques. A dimensionless correlation was also proposed for the prediction of droplet length in which the relative error was 8.2%.